2019
DOI: 10.1002/pi.5816
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency above 6% in poly(3‐hexylthiophene):phenyl‐C‐butyric acid methyl ester photovoltaics via simultaneous addition of poly(3‐hexylthiophene) based grafted graphene nanosheets and hydrophobic block copolymers

Abstract: A combination of reduced graphene oxide (rGO) nanosheets grafted with regioregular poly(3-hexylthiophene) (P3HT) (rGO-g-P3HT) and P3HT-b-polystyrene (PS) block copolymers was utilized to modify the morphology of P3HT:[6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) active layers in photovoltaic devices. Efficiencies greater than 6% were acquired after a mild thermal annealing. To this end, the assembling of P3HT homopolymers and P3HT-b-PS block copolymers onto rGO-g-P3HT nanosheets was investigated, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Due to their excellent properties such as optoelectronic designability, low-cost solution processability, and polymeric flexibility, semiconducting polymers have been extensively researched for many applications in OFETs, , printable integrated circuits, , wearable ultralight sensors, , large-area photovoltaic devices, ,, etc. For example, it was demonstrated that semiconducting conjugate polymer-based solar cells can reach high power conversion efficiencies (PCEs), around 6%. However, the low charge carrier mobilities for semiconducting polymers still restrict their practical applications. It is believed that integrating semiconducting polymers with high-performance conductors is one feasible approach to overcome this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent properties such as optoelectronic designability, low-cost solution processability, and polymeric flexibility, semiconducting polymers have been extensively researched for many applications in OFETs, , printable integrated circuits, , wearable ultralight sensors, , large-area photovoltaic devices, ,, etc. For example, it was demonstrated that semiconducting conjugate polymer-based solar cells can reach high power conversion efficiencies (PCEs), around 6%. However, the low charge carrier mobilities for semiconducting polymers still restrict their practical applications. It is believed that integrating semiconducting polymers with high-performance conductors is one feasible approach to overcome this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper from Xu and coworkers [143], they describe an OPV based on the classic architecture P3HT:PCBM, where a compatible low-bandgap polymer is added, PCBTDPP, in order to act as a "bridge" between the main donor and acceptor units, Block copolymers incorporating both P3HT and poly(styrene) portions are well-known polymeric CBs, widely reported to improve the morphology of P3HT blends in combination with PCBM [140] or other fulleropyrrolidine derivatives [141]. An "exotic" approach has been recently referred to by Mohammadi-Arbati and colleagues, who have reported the combined addition of a rod-coil block copolymer comprising P3HT and polystyrene (P3HT-b-PS), and reduced graphene oxide nanosheets grafted with regioregular poly(3-hexylthiophene) (rGO-g-P3HT) as compatibilizers in a typical P3HT:PCBM blend [142]. A combination of data acquired by XPS, TEM, and AFM supports the hypothesis that the CB localizes at the interface, with P3HT portions from the copolymer interacting with the P3HT residues grafted onto rGO-g-P3HT.…”
Section: Thiophene-containing Polymeric Cbsmentioning
confidence: 99%
“…Some researchers have utilized distinct agents in organic photovoltaics to stabilize the morphology of active layers. [10][11][12][13][14][15][16][17][18][19][20][21] In this regard, the polymer/quantum dot (QD) compositions have retained attention for the morphological and structural manipulations in photovoltaics. [22][23][24][25][26][27][28][29][30] For having the proper carrier generation, cheapness, and optical activities depending on size, the 2 | EXPERIMENTAL CQD preparation.…”
Section: Introductionmentioning
confidence: 99%